A comparison study of the influence of milk protein versus whey protein in high-protein diets on adiposity in rats. Issue 3 (27th January 2021) - Ren, Haoyi; Liu, Tristan C.; Lu, Yipin; Zhang, Kai; Xu, Ying; Zhou, Peng; Tang, Xue
Abstract : 40% MPC reduced the increase in body weight, fat ratio and plasma lipid levels induced by high-fat diet in rats. It also increased the transsulfuration pathway, increasing levels of H2 S, promoting the body's lipid metabolism. Abstract : High-protein diets are known to reduce weight and fat deposition. However, there have been only a few studies on the efficacy of different types of high-protein diets in preventing obesity. Therefore, the emphasis of this study lies in comparing the efficacy of two high-protein diets (milk protein and whey protein) in preventing obesity and exploring specific mechanisms. Eighty Sprague Dawley rats were divided into two groups and fed with milk protein concentrate (MPC) and whey protein concentrate (WPC) for 12 weeks. Each group was divided into four levels: two low-fat regimens with either low or high protein content (L-14%, L-40%) and two high-fat regimens with either low or high protein content (H-14%, H-40%). The studies we have performed showed that rats treated with MPC at the 40% protein level had significantly reduced body weight, fat weight and fat ratio gain induced by a high-fat diet, while the protein level in the WPC group had no effect on body weight or body fat in rats fed with a high-fat diet. What is more, rats fed with MPC at the H-40% energy level showed a significant decrease in plasma triglyceride, total cholesterol and low-density lipoprotein cholesterol levels and a significant increase in plasma high-density lipoprotein cholesterol levels compared with the H-14% energy level group. In contrast, in the WPC groups, increasing the protein content in high-fat diets had no significant influence on plasma lipid levels. The results of the amino acid composition of the two proteins and plasma showed that the MPC diet of 40% protein level increased the transsulfuration pathway in rats, thereby increasing the level of H2 S. This research work has shown that not all types of high-protein diets can effectively prevent obesity induced by high-fat diets, as effectiveness depends on the amino acid composition of the protein.